O modelo de Ohlson aplicado ao mercado de capitais brasileiro para verificar a sinalização dos dividendos no valor e na avaliação das empresas abertas - Cioffi, Patrícia Leite de Moraes (2009)
This study used Ohlson´s model (1995, 2001) of firm valuation, which does connection between accounting data and market values, in order to test the dividend signaling effect in two aspects: in the effective value and in the valuation of Brazilian firms. In the sample it was considered BM&FBovespa listed companies, from 1997 to 2007. First, it was verified if dividends could be considered as a proxy for information that helps predict future abnormal earnings, in order to test the signaling effect in the equity market value of the firms. Further, it was examined the dividend relevance in the analysts forecasts. The purpose was to prove if dividends could have a signaling effect in the analysts valuation, and if they could reduce information asymmetry, that is forecast errors. The results evidenced the dividend positive pricing in the firm values, according to studies made abroad Rees (1997), Fama e French (1998), Giner e Rees (1999) e Akbar e Stark (2003) e Hand e Landsman (2005) and also in Brazil Correia e Amaral (2002), Novis e Saito (2003), Bruni et al. (2003) e Famá et al. (2008). However, this positive result could not be addressed to the signaling effect of future profit expectation. But, the evidences led to consider dividends as relevant to investors because of risk aversion, according to Bird in the Hand Theory, presented by Gordon and Lintner (1968). Regarding the analyst forecasts, the dividend signaling was confirmed. It was found that signaling effect occurred because of the less information asymmetry provided by firms that distribute dividends. It meant that the forecast errors were smaller for these companies. Moreover, the analysts´ future revenue expectations reflected that other information still not figured in the financial statements, beyond past performance and dividends, was not controlled in the adopted model